2018
DOI: 10.1002/ana.25272
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Depdc5 deletion recapitulates electroclinical features of human focal cortical dysplasia type IIA

Abstract: Epileptogenic mechanisms in focal cortical dysplasia (FCD) remain elusive, as no animal models faithfully recapitulate FCD seizures, which have distinct electrographic features and a wide range of semiologies. Given that DEPDC5 plays significant roles in focal epilepsies with FCD, we used in utero electroporation with clustered regularly interspaced short palindromic repeats gene deletion to create focal somatic Depdc5 deletion in the rat embryonic brain. Animals developed spontaneous seizures with focal patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 22 publications
5
61
0
Order By: Relevance
“…Most of the experiments defining the components of the amino acid modulatory arm of the mTOR pathway have been performed in non‐neuronal cell lines. Recent studies in neurons, however, have shown how DEPDC5 and NPRL3 may modulate neural activity and epileptogenesis . A recent study demonstrated that knockdown of Depdc5 or Nprl3 caused mTOR‐dependent increases in cell size and process outgrowth in Neuro2a cells (N2a cells; a neuroblastoma cell line) and in mouse neural progenitor cell .…”
Section: Cell Biology Of the Gator1 Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the experiments defining the components of the amino acid modulatory arm of the mTOR pathway have been performed in non‐neuronal cell lines. Recent studies in neurons, however, have shown how DEPDC5 and NPRL3 may modulate neural activity and epileptogenesis . A recent study demonstrated that knockdown of Depdc5 or Nprl3 caused mTOR‐dependent increases in cell size and process outgrowth in Neuro2a cells (N2a cells; a neuroblastoma cell line) and in mouse neural progenitor cell .…”
Section: Cell Biology Of the Gator1 Complexmentioning
confidence: 99%
“…Two recent studies using CRISPR‐editing of Depdc5 in the rodent cerebral cortex demonstrated abnormal electrical bursts and clinical seizures associated with experimentally induced FCD following CRISPR‐editing of Depdc5 by in utero electroporation . In a rat model two short guide RNAs (gRNAs) were used to target rat Depdc5 either at exon 8 or exon 12 by in utero electroporation on embryonic day 13. Analysis of these animals on postnatal day 21 revealed enlarged neuronal somata in association with hyperactivated mTORC1.…”
Section: Epileptogenesis and Mtor‐gator Signalingmentioning
confidence: 99%
“…The specific morphology and dynamic behavior of oRG cells contribute to the proliferative expansion of the cortex and provide a scaffold upon which neuronal migration of the cortex depends. pathway in mouse models have identified phenotypic changes to neuronal size, morphology, and laminar position that resemble disease features of cortical malformations (Hu et al, 2018;Nguyen et al, 2019;Park et al, 2018). However, questions remain regarding the effects of mTOR dysregulation on progenitor cells as well as relevant differences between human and mouse cortical development.…”
Section: Introductionmentioning
confidence: 99%
“…In utero electroporation approaches offer an elegant means of modeling the effects of somatic mutations arising in the fetal cortex in a focal subset of neural cells at varying developmental time-points. CRISPR-mediated gene deletion of DEPDC5 in rats (Hu et al, 2018) and activation of mTOR signaling in mice using constitutively active mTOR kinase or Rheb proteins (Lim et al, 2015;Nguyen et al, 2019) have been shown to cause abnormal neuronal morphology and migration defects in the developing cortex. Furthermore, the severity of the seizure phenotype appears to correlate well with the extent of the electroporation, providing evidence linking the severity of malformations with the timing of the mutagenic event.…”
Section: Mtoropathies and Progenitor Cellsmentioning
confidence: 99%